Infant botulism: an underestimated problem. A review - Valeri A. Malov; Viktor V. Maleev; Vladimir P. Chulanov; Denis S. Sarksyan (Терапевтический архив)
The article is devoted to a form of botulism that has been little studied in our country and is registered exclusively in infants. The fundamental difference between this form and the most common foodborne botulism is that infants become infected by ingestion of spores, followed by their germination, colonization of the intestines and production of botulinum toxin in situ, which leads to the development of life-threatening flaccid paralysis. Taking into account the peculiarities of pathogenesis, the clinical manifestations of infant botulism have some features, which are discussed by the authors. Particular attention is paid to the epidemiology and risk factors for the development of the disease. The article discusses in detail the issues of diagnosis and laboratory verification of the etiology of the disease. Current data on the treatment of infant botulism are presented.